2015
DOI: 10.1177/070674371506000504
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to First-Episode Care for Psychosis in African-, Caribbean-, and European-Origin Groups in Ontario

Abstract: Objective: To compare the pathways to care and duration of untreated psychosis (DUP) for people of Black-African, Black-Caribbean, or White-European origin with first-episode psychosis (FEP). Methods:We recruited a sample of 171 patients with FEP of Black-African, Black-Caribbean, and White-European origin from hospital-and community-based early intervention services (EIS) in the cities of Toronto and Hamilton. We compared the 3 groups on DUP and key indicators of the pathway to care. Results:We observed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 43 publications
6
58
0
2
Order By: Relevance
“…A detailed overview of the data collection procedure is described elsewhere. 13 Briefly, each interview took between 1.5 and 2 h to complete and was conducted by a trained research assistant. The pathways to care were measured using the Encounter Form, 16 which gathered information on encounters with any type of health or social service provider.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed overview of the data collection procedure is described elsewhere. 13 Briefly, each interview took between 1.5 and 2 h to complete and was conducted by a trained research assistant. The pathways to care were measured using the Encounter Form, 16 which gathered information on encounters with any type of health or social service provider.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…9 Within the Canadian context, there is evidence to suggest that individual and clinical factors may influence pathways to care. [10][11][12][13] However, a recent study conducted by Anderson and colleagues (2013) concluded that service-level factors may play a more important role. The authors found that people who consulted a general practitioner (GP) were more likely to have two or more contacts in their pathway to care and were also less likely to have police involvement.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recruitment for this study occurred via the Toronto Early Intervention in Psychosis Network and Hamilton's Cleghorn Early Intervention Program between April 2011 and April 2013 and is described in detail elsewhere. 21 Informed consent was received from each participant. The Research Ethics Boards at the Centre for Addiction and Mental Health and other participating hospital sites approved this study.…”
Section: Study Samplementioning
confidence: 99%
“…23 Information was obtained on sociodemographic factors (Table 1), immigration status, symptom profiles and explanatory models of illness. 21 Participants were asked to self-identify as either black African, black Caribbean or white European. Immigration status was determined using the birthplace of the participant and his/her parents.…”
Section: Data Collectionmentioning
confidence: 99%
“…Prior qualitative studies have identified a number of factors that can influence pathways to care and delays in treatment (Anderson et al, ; Anderson, Fuhrer, & Malla, ; Ben‐David, Cole, Brucato, Girgis, & Munson, ; Boydell, Gladstone, & Volpe, ; Cabassa et al, ; Cadario et al, ; Ferrari et al, ; Ferrari et al, ; Jansen, Pedersen, Hastrup, Haahr, & Simonsen, ; Judge, Estroff, Perkins, & Penn, ; Tanskanen et al, ); however, two‐thirds of these studies took place outside the United States, and most reflect the experiences of patients who sought care in specialty EI programs. Barriers to care seeking may differ in settings where EI programs are inaccessible or unavailable.…”
Section: Introductionmentioning
confidence: 99%